Antiobesity effect of Gynostemma pentaphyllum extract (actiponin): A randomized, double‐blind, placebo‐controlled trial. (5th September 2013) - Park, Soo‐Hyun; Huh, Tae‐Lin; Kim, Sun‐Young; Oh, Mi‐Ra; Tirupathi Pichiah, P.B.; Chae, Soo‐Wan; Cha, Youn‐Soo
Abstract : Objective: The effects of actiponin was investigated, a heat‐processed Gynostemma pentaphyllum extract, on body weight, fat loss, and metabolic markers of Korean participants in a 12‐week, randomized, double‐blind, placebo‐controlled clinical trial. Design and Methods: Obese participants (BMI ≥ 25 kg m −2 and WHR ≥ 0.90 for male or WHR ≥ 0.85 for female) who had not been diagnosed with any disease and met the inclusion criteria were recruited for this study. The 80 subjects were randomly divided into actiponin ( n  = 40, 450 mg day −1 ) and placebo ( n  = 40) groups. Outcomes included measurement of efficacy (abdominal fat distribution, anthropometric parameters, and blood lipid profiles) and safety (adverse events, laboratory test results, electrocardiogram data, and vital signs). Results: During 12‐week of actiponin supplementation, total abdominal fat area, body weight, body fat mass, percent body fat, and BMI were significantly decreased ( P  = 0.044, P  < 0.05, P  < 0.0001, P  < 0.0001, and P  < 0.05, respectively) in the actiponin group compared to the placebo group. No clinically significant changes in any safety parameter were observed. Conclusion: Our study revealed that actiponin is a potent antiobesity reagent that does not produce any significant adverse effects. These results suggest that actiponin supplementation may be effective for treating obese individuals.